2021
DOI: 10.1007/s10853-021-06082-y
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of cellulose nanofibrils and silver nanowires for the development of screen-printed antibacterial surfaces

Abstract: TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl)-oxidized cellulose nanofibrils (T-CNF) and silver nanowires (Ag NWs) were formulated as active inks. Their rheological properties were investigated to design optimal conditions for processing by the screen-printing process, with the aim of preparing antibacterial patterns. Rheological experiments mimicking the screen-printing process was applied to different ink formulations to investigate their thixotropic and viscosity properties. The experiments conducted at 1% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Nevertheless, some defects restrict the commercial application of AgNW TCFs, including difficulty in largescale production, personalized pattern and precision printing [25,26]. Currently, ultrasonic spray coating [27][28][29][30], spin coating [21], slot coating [31][32][33] and screen printing [7,[34][35][36][37][38][39][40][41][42][43][44] have been used for the large-scale production of high-quality TCFs. Wherein, ultrasonic spraying as an efficient method to produce large-sized TCFs, while it has to face with defects such as high surface roughness and poor uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some defects restrict the commercial application of AgNW TCFs, including difficulty in largescale production, personalized pattern and precision printing [25,26]. Currently, ultrasonic spray coating [27][28][29][30], spin coating [21], slot coating [31][32][33] and screen printing [7,[34][35][36][37][38][39][40][41][42][43][44] have been used for the large-scale production of high-quality TCFs. Wherein, ultrasonic spraying as an efficient method to produce large-sized TCFs, while it has to face with defects such as high surface roughness and poor uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Suresh et al [ 19 ] reported biofabrication of silver nanocrystallites using Shewanella oneidensis, which indicated favorable antibacterial properties for Gram-negative and Gram-positive bacteria [ 19 ]. Resistance to silver-based compounds is rare in organisms, especially Gram-negative bacteria [ 20 ]. Bacteria destroyed by silver could possess 10 5 –10 7 Ag + molecules per cell, which is the same order of magnitude as the predicted number of enzyme-protein molecules per cell.…”
Section: Strategies For Achieving Antibacterial Biomaterialsmentioning
confidence: 99%
“…Wilson and Boland modified the HP printer and developed the first inkjet bioprinter in 2003 [ 16 ]. These 3D printing techniques allow for the creation of customized patient-specific designs with a large scale of reproduction, as well as the incorporation of cells, if needed, to form cell-laden matrices or constructs of various TE applications [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Understanding how these functional films are formed during the evaporation of colloidal droplets is critical for many applications related to microfluidics, [3,4,12,14] inkjet printing, [15][16][17] printed electronics, [18,19] and the synthesis of biomaterials. [20][21][22] Silver (Ag) based inks are often used for printed electronics, [16,[23][24][25] sensor fabrication, [26,27] producing antimicrobial materials, [28][29][30] and manufacturing solar cells. [31] Silver is preferred for these applications because of its outstanding electrical conductivity, [16,23,24] high heat transfer capabilities, [25,32] and robust mechanical properties.…”
Section: Introductionmentioning
confidence: 99%